2001
DOI: 10.1029/2000gl012485
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of reverse polarity TCRs

Abstract: Abstract.Reverse polarity, or South-then-North (SN) bipolar, traveling compression regions (SN TCRs) are often observed in the Earth's magnetotail lobes. These events have been interpreted as either slowly earthward propagating "proto-plasmoids" during extremely quiet geomagnetic conditions, or due to pressure pulses in the solar wind or magnetosheath compressing the magnetotail. This study presents a survey of 21 IMP 8 observations of SN TCRs and the corresponding solar wind pressure conditions as measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…The mean compression of these tailward propagating TCRs was B/B=7.6% with a duration of 158 s. The size of these plasmoids was estimated by the TCR amplitude and duration to be approximately 35 R E in x-and 15 R E in y-and z-direction. IMP 8 observations in the mid-tail gave first evidence of the existence of earthward propagating TCRs (Moldwin and Hughes, 1994;Moldwin et al, 2001), which was supported by Cluster observations in the near tail at X>−20 R E . These near tail TCRs (Slavin et al, 2003c;Borälv et al, 2005;Sergeev et al, 2005;Owen et al, 2005) strongly resemble those in the distant tail.…”
Section: Introductionsupporting
confidence: 54%
“…The mean compression of these tailward propagating TCRs was B/B=7.6% with a duration of 158 s. The size of these plasmoids was estimated by the TCR amplitude and duration to be approximately 35 R E in x-and 15 R E in y-and z-direction. IMP 8 observations in the mid-tail gave first evidence of the existence of earthward propagating TCRs (Moldwin and Hughes, 1994;Moldwin et al, 2001), which was supported by Cluster observations in the near tail at X>−20 R E . These near tail TCRs (Slavin et al, 2003c;Borälv et al, 2005;Sergeev et al, 2005;Owen et al, 2005) strongly resemble those in the distant tail.…”
Section: Introductionsupporting
confidence: 54%
“…Such SN TCRs had been noted earlier [ Slavin et al , 1993], but they had been attributed to external compression of the tail lobes by short duration enhancements of solar wind pressure. In fact, Moldwin et al [2001] examined 21 SN TCRs and found that 17 were associated with short duration upstream solar wind pressure increases. However, they suggested that the remaining 4 events might be due to the Earthward moving “plasmoids”.…”
Section: Discussionmentioning
confidence: 99%
“…The lobe FTE‐type TCRs consist of several‐seconds‐long compressive perturbations with the ± B 1 normal field variation signaling their tailward motion [ Russell and Elphic , 1978; Russell and Walker , 1985, Wang et al , 2005]. FTE‐type flux ropes (Figure 6c) observed several minutes later are identified by the ± B 1 perturbation indicating tailward motion and their associated unipolar core field [ Moldwin et al , 2001; Liu et al , 2008]. When minimum variance analysis is performed on individual flux ropes, the unipolar core field increase appears in the B 2 direction as expected [ Russell and Elphic , 1978].…”
Section: Fte Shower Of 11 April 2011mentioning
confidence: 99%